Sistem Aplikasi Supervisi Kunjungan Kelas pada Guru Madrasah di Kota Banda Aceh - Agussalim, Agussalim (Tadabbur: Jurnal Peradaban Islam, 2022)
Educational process is acceleration of the globalization of technology education system that demands to be able to collaborate as a new era of educational development, especially in the supervision of learning, for supervised learning the technique, especially in supervising classroom must adjustments to the way in providing surveillance technology utilizing information technologybased teaching. This study focuses on how to design an application system supervisory class visits and how to test its performance. The goal this application is to be supervision media to effective supervisor, and to efficient supervisor duty to supervision to madrasah at Banda Aceh. This study using methods of descriptive, evaluative, and experimental, as study materials, the data collected through observation, interviews, and documentation are analyzed descriptively by means of inductive thinking. While the methods used in building applications system design is based on a structured approach is by using the waterfall method, a tool for designing applications in the form of Map Data Flow and Data Flow Diagram. While supporting software uses Microsoft Excel as a spreadsheet application program that is familiar among the data processing and calculation reports. Based on the results of the development through the design and testing of application programs on a madrasah classroom supervision in Banda Aceh, the results showed: 1) Development of application program supervision to the madrasah classes in Banda Aceh has been through a series of software engineering process from design to testing in accordance with the needs of supervisors in evaluating the quality of teaching and learning processes of teachers; 2) the performance of the overall application program can work in accordance with their respective functions that can help supervisors, fast, precise, and accurate.